Oral health status of 5, 12, and 15-year-old school children in Tiruvalla, Kerala, India - Benley George; Vinod Mathew Mulamoottil (Wolters Kluwer Medknow Publications, 2015)
Background: Dental caries can be traced to be as old as civilization with its evidence seen even in skeletal remnants of prehistoric humans. Dental caries is the most prevalent dental affliction of childhood. Materials and Methods: A stratified cluster sampling technique was employed in the selection of 39 schools in the geographical region. A total of 5688 students was screened. Of the total students screened, 1623 students were 5-year-old, 1936 were 12-year-old and 2129 were 15-year-old students. Pearson Chi-square test and Fishers exact test were the statistical tests employed in the survey. The level of significance was set to be P < 0.05. Results: The present study revealed that the majority (73.9%) of the 12 years students had healthy gingiva. It was revealed that among girls, 21.8% had calculus, and 2.5% had bleeding gums. Among boys, 24.3% had calculus, and 3.1% had bleeding gums. The prevalence of dental caries was the highest among 5 years students who belonged to the lower socioeconomic status (41.5%). The difference was found to be statistically significant (P = 0.004). The mean decayed, missing, and filled teeth was found to be the highest in students of 5 years age group when compared to their counterparts (P = 0.041). Conclusion: The study reveals that dental caries still remains as a major oral health problem among school children of all age group. Gingival problems also formed one of the major oral health problems of 12 and 15-year-old school children.